Desenvolvimento de uma antena impressa sub-GHz encapsulada com dimensões reduzidas - Ribeiro, Maurício Carlotto (Universidade do Vale do Rio dos Sinos, 2021)
Since the realization of the first effective communication between wireless devices, many technologies have emerged to fill the most variety of markets and opportunities, which has made the term “portable” increasingly frequent and necessary in product development. Over this road, antennas have always remained present as they are an essential part of the whole system that allows the transmission and reception of signals. However, the technologies employed in the antenna’s development did not follow the same evolution speed as the RF (Radio Frequency) circuits, which became increasingly reduced. Thus, printed antennas began to receive greater importance as it was possible to include them in the device without occupying a significantly large area. Nevertheless, it appears that the development of radios with integrated antennas represents a potentially viable proposal in the sense of providing a ready-made wireless communication structure in a single package. In this context, this work aims to develop a small, encapsulated antenna for Internet of Things products, focusing on technologies that uses sub-GHz frequencies. The proposal consists in overcoming the physical limitations through antenna miniaturization methodologies, in order to produce a printed antenna model that can be encapsulated with the circuit to which it belongs. The first work consisted in the evaluation of different antenna designs through electromagnetic simulations, which allowed establishing their electrical characteristics and choosing the one that presents the best possibility of being encapsulated and offering a good performance. Two miniaturization methodologies were chosen and tested separately through simulations: the use of substrates with high dielectric constant and the application of Fractal geometries. The simulation results showed that the replacement of common meanders by the Hilbert-type Fractal Geometry in an inverted F Antenna was able to obtain a reduction of up to 44.45% of the original dimensions, but with some punctual performance reductions. Prototypes were manufactured to evaluate the results obtained in software, however, the measurements showed inconsistency with values verified in simulation. Thus, it was necessary to adjust the characteristics of the prototypes through physical adjustments and the addition of matching networks, thus allowing the expected performance to be achieved and even improving some characteristics. Communication evaluations were conducted using manufactured antennas and test equipment, which endorse the conclusion that the miniaturization process allowed the development of small antennas, including manually encapsulated, which are capable of transmitting and receiving signals from RF successfully.
Keywords: Antena encapsulada; UHF; Fractal; Miniaturização; Internet das coisas; Sub-GHz; Antena impressa; Encapsulated antenna; Miniaturization; Internet of things; Printed antenna; ACCNPQ::Engenharias::Engenharia Elétrica